Effectiveness of the Implementation of the Marriage Law on Child Protection After a Divorce Decision - Lesmana, Rico; Arpangi, Arpangi (UNISSULA Semarang, 2025)
Abstract. The objectives of this research are: to understand and analyze how child protection is implemented after a divorce, how the rights and obligations of parents toward their child are fulfilled after the divorce, and what solutions can be proposed. The research approach used in this study is a normative juridical approach, which is a process of discovering legal norms, legal principles, and legal doctrines to address the legal issues at hand. Law Number 16 of 2019 aims to protect children after divorce, but its implementation still faces various obstacles. The main challenges include a lack of socialization and public understanding of children's rights, limited access to legal services, as well as complex and slow legal bureaucracy. Although regulations regarding custody, alimony, and child care are clearly stated, their practice remains suboptimal. Therefore, improvements in education, training for relevant parties, simplification of procedures, and expansion of legal access are needed to ensure maximum child protection. The government and law enforcement must enhance public awareness and understanding of children's rights after divorce and the implementation of Law No. 16 of 2019 through media, seminars, and training. Legal services must be easily accessible and of high quality for families going through divorce. Law enforcers, courts, and social workers need intensive training to provide accurate information. Parents are also expected to actively seek information, maintain communication, and prioritize the psychological well-being and interests of the child during and after the divorce process.